2006
DOI: 10.1007/s00239-005-0223-z
|View full text |Cite
|
Sign up to set email alerts
|

The Repetitive DNA Elements Called CRISPRs and Their Associated Genes: Evidence of Horizontal Transfer Among Prokaryotes

Abstract: Abstract. We have found direct DNA repeats 21-47 bp in length interspersed with nonrepetitive sequences of similar length, or clustered regularly interspaced short palindromic repeats (CRISPRs) in a wide range of diverse prokaryotes, including many Archaeal and Eubacterial species. A number of cas, CRISPR-associated genes have also been characterized in many of the same organisms. Phylogenetic analysis of these cas genes suggests that the CRISPR loci have been propagated via HGT, horizontal gene transfer. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
248
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(283 citation statements)
references
References 16 publications
21
248
1
6
Order By: Relevance
“…Cas1, cas3, and cas4 proteins are homologous to a DNA repair protein, a helicase, and recB exonuclease, respectively. The predicted proteins of this study are directly contributed in DNA a repair and recombination mechanism, which was agreed to earlier annotation (Brügger et al 2002;Sasaki et al 2004;Godde and Bickerton 2006;Weinberger et al 2012;Quax et al 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cas1, cas3, and cas4 proteins are homologous to a DNA repair protein, a helicase, and recB exonuclease, respectively. The predicted proteins of this study are directly contributed in DNA a repair and recombination mechanism, which was agreed to earlier annotation (Brügger et al 2002;Sasaki et al 2004;Godde and Bickerton 2006;Weinberger et al 2012;Quax et al 2013).…”
Section: Discussionsupporting
confidence: 91%
“…CRISPR loci have shown a distinct genetic and molecular diversity in the strains of a thermophilic archaean, Methanocaldococcus jannaschii (Bult et al 1996) and of thermophilic bacterium, Streptococcus thermophilus (Horvath et al 2008). Some of the CRISPR sequences in Thermoanaerobacter tengcongensis and Thermus thermophilus HB8 chromosomes have shared with their existing megaplasmids (Jansen et al 2002;Godde and Bickerton 2006). Spacer sequences have also shown a variation in five strains of Thermotoga neapolitana by geographic locale (DeBoy et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, the repeats tend to vary between distantly-related species, but exceptions are often noted; for example, the arrays in Escherichia coli and Mycobacterium avium contain very similar repeats, although these two organisms are classified in different phyla 14 . This has been explained by horizontal gene transfer of CRISPR systems between organisms, a hypothesis supported by phylogenetic trees of core CAS genes 16,17,22 . Gene transfer was suggested to be mediated by megaplasmids, based on the identification of 10 such plasmids carrying CRISPR arrays 22,33 .…”
Section: Evolution Of Crispr Systemsmentioning
confidence: 99%
“…This has been explained by horizontal gene transfer of CRISPR systems between organisms, a hypothesis supported by phylogenetic trees of core CAS genes 16,17,22 . Gene transfer was suggested to be mediated by megaplasmids, based on the identification of 10 such plasmids carrying CRISPR arrays 22,33 . Interestingly, a CRISPR array was also found within a Clostridium difficile prophage, and it was suggested that the phage uses the CRISPR to limit dispersal of competing phages 34 .…”
Section: Evolution Of Crispr Systemsmentioning
confidence: 99%
See 1 more Smart Citation